2021
DOI: 10.1002/adfm.202103119
|View full text |Cite
|
Sign up to set email alerts
|

Grain Boundaries in Cu(In, Ga)Se2: A Review of Composition–Electronic Property Relationships by Atom Probe Tomography and Correlative Microscopy

Abstract: Cu(In,Ga)Se 2 thin-film solar cells have attracted significant research interest in recent decades due to their high efficiency in converting solar energy into electricity for enabling a sustainable future. Although the Cu(In,Ga)Se 2 absorber can be grown as a single crystal, its polycrystalline form is dominating the market not only due to its lower costs, but also due to its unexpectedly higher cell efficiency. However, this absorber contains a high fraction of grain boundaries. These are structural defects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 193 publications
(567 reference statements)
4
46
0
Order By: Relevance
“…Recently, we have implemented a parameter called the Cu factor (Δβ), [ 19 ] which is defined as the difference in composition changes (Δ = (composition at GB) − (composition in GI)) at a GB between Cu and Se + In + Ga: Δβbadbreak=ΔCugoodbreak−false(ΔSegoodbreak+ΔIngoodbreak+ΔGafalse)\[\Delta \beta = \Delta {\rm{Cu}} - (\Delta {\rm{Se}} + \Delta {\rm{In}} + \Delta {\rm{Ga}})\] …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we have implemented a parameter called the Cu factor (Δβ), [ 19 ] which is defined as the difference in composition changes (Δ = (composition at GB) − (composition in GI)) at a GB between Cu and Se + In + Ga: Δβbadbreak=ΔCugoodbreak−false(ΔSegoodbreak+ΔIngoodbreak+ΔGafalse)\[\Delta \beta = \Delta {\rm{Cu}} - (\Delta {\rm{Se}} + \Delta {\rm{In}} + \Delta {\rm{Ga}})\] …”
Section: Resultsmentioning
confidence: 99%
“…[35] GBs have been intensively studied for Cu-poor CIGS systems by various groups, and a recent comprehensive review summarizing all existing works can be found in ref. [19]. However, no publication exists yet on GBs in Cu-rich CIGS absorbers.…”
Section: Grain Interior and Grain Boundariesmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, very recently, substantial efforts have been put forth to reveal if a correlation or a rather coincidence relationship exists between the composition and several materials properties, such as optical/electrical and structural properties. These efforts have led to novel methodologies called correlative EBIC-EBSD-APT, 24,25 where EBIC stands for electron-beam-induced current.…”
Section: Introductionmentioning
confidence: 99%